Prognostic effects of clinical parameters, genetic abnormalities, and subtypes in primary gastric diffuse large B-cell lymphoma: a cohort analysis of 146 patients. Issue 14 (6th December 2022) - Liu, Junqing; Wei, Juying; Jiang, Xue; Yu, Wenjuan; Tong, Hongyan; Jin, Jie; Yan, Senxiang; Xu, Weilai
Abstract: This study included 146 primary gastric diffuse large B-cell lymphoma patients. Next-generation RNA sequencing and fluorescent in situ hybridization were performed on tumors from 27 and 38 patients, respectively. Five-year and 10-year overall survival (OS) rates were 77% and 57%, respectively. Lugano and TNM clinical stage were independent survival factors. Tier I mutation was found in 21 patients. The genetic subtypes were A53 ( n = 3), MCD ( n = 5), BN2 ( n = 5), N1 ( n = 5), EZB ( n = 1), and NOS ( n = 8). OS was significantly shorter in high-risk genetic subtypes (A53, MCD, and N1) than low-risk subtypes (BN2, EZB, and NOS). Frequencies of high-risk genetic subtypes were higher in patients with Lugano stage II/IV and TNM clinical stage III + IV than in those with Lugano stage I and TNM clinical stage I + II. Although genetic testing was performed in only a small number of cases, the results suggested that high-risk genetic subtypes were associated with advanced clinical stages and shorter survival.